INTEGRATIVE AND INTERDISCIPLINARY APPROACHES TO THE TEACHING OF GNOSEOLOGY (Eureka Journal of Education & Learning Technologies, 2026)
This scientific article examines modern methods of teaching epistemology in the higher education system, in particular, integrative and interdisciplinary approaches. The author substantiates the need to ensure the interaction of philosophy with such areas as psychology, cognitive sciences, neuroscience, linguistics, pedagogy, and artificial intelligence for the effective acquisition of epistemological knowledge. The article reveals the theoretical foundations, didactic possibilities, and practical implementation methods of integrative and interdisciplinary approaches. In addition, the role of these approaches in developing students' critical thinking, forming a scientific worldview, and improving decision-making skills in conditions of uncertainty is analyzed. Based on the results of the study, practical recommendations for improving the teaching of epistemology are developed.
Keywords: Epistemology, theory of knowledge, integrative approach, interdisciplinary approach, philosophy education, critical thinking, cognitive sciences, higher education, methodology, innovative technologies.